2020
DOI: 10.1053/j.gastro.2020.05.080
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Redox and Protein Homeostasis as Risk Factors and Therapeutic Targets in Toxin-Induced Biliary Atresia

Abstract: BACKGROUND and AIMS: Extra-hepatic biliary atresia (BA) is a pediatric liver disease with no approved medical therapy. Recent studies using human samples and experimental modeling suggest that glutathione redox metabolism and heterogeneity play a role in disease pathogenesis.We sought to dissect the mechanistic basis of liver redox variation and explore how other stress responses affect cholangiocyte injury in BA. METHODS:We performed quantitative in situ hepatic glutathione redox mapping in zebrafish larvae c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…A limitation of this study was the small sample size, which precluded confirmative statistical evidence for two of our hypotheses: first, the existence of a correlation between HIF-nuclear positivity in cholangiocytes and decreased early native liver survival; and second, that reduced native liver survival might have resulted from the loss of the protective role of GSR against oxidative stress, as observed in an experimental model of BA [60]. However, given the small size of the sample, for both these correlations we were only able to detect a trend for statistical significance (SDC2 Table 5…”
Section: Discussionmentioning
confidence: 92%
“…A limitation of this study was the small sample size, which precluded confirmative statistical evidence for two of our hypotheses: first, the existence of a correlation between HIF-nuclear positivity in cholangiocytes and decreased early native liver survival; and second, that reduced native liver survival might have resulted from the loss of the protective role of GSR against oxidative stress, as observed in an experimental model of BA [60]. However, given the small size of the sample, for both these correlations we were only able to detect a trend for statistical significance (SDC2 Table 5…”
Section: Discussionmentioning
confidence: 92%
“…22,23 The inhibition of HSP90 can also prevent LPS-induced liver injury by decreasing proinflammatory cytokines in mice. 24 Besides, HSP90 might be involved in the injury of cholangiocytes in patients with biliary atresia 25 and is a potential biomarker for the diagnosis of biliary atresia. 26 In this study, we found that a high expression of HSP90 could mediate cholangiocyte necroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it seems to be multifactorial. Other than a viral involvement with sporadic cases including reovirus, rotavirus, Epstein-Barr virus, and cytomegalovirus, a decreased Treg subset of the CD4 positive T lymphocytes [ 70 , 71 ], environmental factors, such as biliatresone [ 59 , 72 , 73 , 74 , 75 ], and ADP-ribosylation factor 6 (ARF6) have been actively investigated [ 76 ].…”
Section: Non-genetic Ambiguitiesmentioning
confidence: 99%